Rehabilitation of degraded Malaysian tropical forests & soil carbon storage - Haruna, Ahmed Osumanu; Ch’ng, Huck Ywih; Ab Majid, Nik Muhammad (Universiti Putra Malaysia Press, 2012)
This book focuses on global carbon emissions and its causes. It encompasses discussions on how forest depletion, due to logging and shifting cultivation, affects soil carbon storage and global warming. Further, the discussions on the significance of soil carbon pools, strategy for carbon sequestration, factors affecting the soil carbon stock in forests and the effect of humic substances on carbon sequestration, in this book, are related to mitigation of the global warming problem. It also highlights the soil evaluation factors used to assess the fertility of tropical soils. This book includes the findings from numerous studies on degraded forest rehabilitation programmes and their effects on soil carbon storage. This book will be of significant interest to those in the field of environmental sciences, foresters, students,research scientists, farmers, environmentalists and others.